Synthesis of highly doped Nd:YAG powder by the SOL-GEL method - Hajiesmaeilbaigi, F.; Farmahini, M. F.; Hasani, J.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
The sol-gel method was used for synthesizing Nd:YAG powder. The process contains several steps, for example solving in acid, mixing, evaporation etc. The XRD analysis of prepared powder by sol-gel method showed that the YAG single phase is resulted by heat treatment at 900 ºC for 2 hr. By SEM the homogeneity of Nd distribution in the YAG lattice was observed.